Digital Agriculture Profile: Viet Nam - Burra, Dharani Dhar; Hildebrand, Jack; Giles, James; Nguyen, Thuy; Hasiner, Eva; Schroeder, Kateryna; Treguer, David; Juergenliemk, Armine; Horst, Alexandra; Jarvis, Andy; Kropff, Wietske (Food and Agriculture Organization of the United Nations, 2021)
Digital technologies are slowly spreading in agriculture sectors globally. But their adoption is hampered by the digital divide which requires significant public investments, improved policy and incentive frameworks to be bridged. Only after that, digital transformation will take place at scale. Digital Agriculture Profile (DAP) is meant to assess the country's readiness for this digital transformation by identifying main bottlenecks, opportunities and risks for digital transformation. DAP will thus guide public investment and policy work to accelerate the scaling up of digital transformation.